Light-humidity response MOFs composite material as well as preparation method and application thereof
By developing light-wet-responsive MOFs composite materials, the dual advantages of light energy and humidity are used to solve the problem of degradation in the presence of water vapor, and the high-efficiency and low-energy consumption of CO2 adsorption effect is achieved, and it is suitable for industrial flue ducts. Fields such as air and air separation.
Patent Information
- Application Number
- CN202411747056.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
AI Technical Summary
The structural stability and CO2 adsorption and separation performance of existing MOFs materials will be affected when water vapor exists, and traditional adsorption and separation technologies have problems of high energy consumption and low efficiency.
Develop a light-wet-responsive MOFs composite material, through reasonable structural design and material composite, realize the dual utilization of light energy and humidity, adjust the adsorption performance, and enhance the CO2 adsorption capacity. Specific methods include microwave synthesis using compounds such as ZrCl4, 2-aminoterephthalic acid, tetrakis(4-carboxyphenyl)porphyrin, Eu(NO3)3·6H2O, acetic acid and DMF to prepare a composite material for light-wet-responsive MOFs.
Under the conditions of changing light and humidity, the adsorption capacity of CO2 is significantly improved, the energy consumption cost of traditional adsorption technology is reduced, and it is in line with the concept of green and sustainable development. It is suitable for industrial flue gas and air separation and other fields.
Smart Images

Figure CN119425644A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material science and environmental engineering, and in particular relates to a light-humidity responsive MOFs composite material and a preparation method and application thereof. Background Art
[0002] With the acceleration of the industrialization and modernization of human society, the rapid economic development and the increasing global population, the intensity of resource and energy consumption has increased significantly, and carbon dioxide emissions have increased rapidly. The concentration of carbon dioxide in the atmosphere has soared from about 350ppm in 1990 to about 420ppm in 2023. As the most important greenhouse gas, excessive emissions of carbon dioxide will produce a "greenhouse effect", causing global warming, and then leading to climate change, ocean acidification, sea level rise, glacier melting, species extinction, etc., which will have a series of major impacts on the ecological environment and human life.
[0003] In recent years, Metal Organic Frameworks (MOFs), as an emerging family of porous functional materials, are mainly zeolite-like materials formed by self-assembly of organic ligands and metal ions through coordination. Compared with traditional adsorbent materials, this type of new material has the characteristics of high specific surface area, controllable porosity, regular pore structure and surface modifiability, which makes it have great application prospects and development potential in CO2 adsorption and separation. However, in actual application scenarios, water vapor inevitably exists in the atmosphere, natural gas and industrial flue gas. The presence of water vapor not only directly affects the structural stability of MOFs, but also affects the adsorption and separation performance of MOFs for CO2. It will be a very challenging topic to study a new solid porous adsorbent material that transforms the unfavorable competitive adsorption of water vapor into a favorable synergistic adsorption.
[0004] In addition, traditional adsorption separation technologies such as pressure swing adsorption and temperature swing adsorption have problems such as high energy consumption and low efficiency. As an emerging adsorbent, photoresponsive MOFs materials can induce internal changes in the material through light irradiation and adjust the adsorption performance, showing great application potential. However, current photoresponsive MOFs materials are often limited to a single photoresponsive characteristic, and the improvement of adsorption performance is limited. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a light-humidity responsive MOFs composite material and its preparation method and application. The material can not only improve the adsorption performance under light conditions, but also respond to humidity changes to further enhance the adsorption capacity of CO2. Through reasonable structural design and material composite, the dual utilization of light energy and humidity is achieved, and the CO2 adsorption efficiency and selectivity are improved.
[0006] To achieve the above object, the present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0007] (1) ZrCl4, 2-aminoterephthalic acid and tetrakis(4-carboxyphenyl)porphyrin are placed in a microwave reaction tube, N,N-dimethylformamide (DMF) and acetic acid are added, and stirred to obtain a solution;
[0008] (2) adding Eu(NO3)3·6H2O to the solution in step (1) and continuing stirring to obtain a mixed solution;
[0009] (3) moving the mixed solution into a microwave reactor and performing microwave synthesis to obtain a reaction product;
[0010] (4) The reaction product obtained in step (3) is centrifuged, washed with ethanol and vacuum dried to obtain a light-moisture responsive MOFs composite material.
[0011] Furthermore, the molar ratio of ZrCl4, Eu(NO3)3·6H2O, 2-aminoterephthalic acid, tetrakis(4-carboxyphenyl)porphyrin, acetic acid and DMF is (1.1-1.5):(0.2-0.8):1:(0.15-0.2):(30-60):(220-300).
[0012] Furthermore, in step (1), the stirring reaction is carried out at room temperature for 10-25 minutes.
[0013] Furthermore, in step (2), the stirring reaction is carried out at room temperature for 10-25 minutes.
[0014] Furthermore, in step (3), the microwave synthesis conditions are 110-130° C. for 1-4 h.
[0015] Furthermore, in step (4), the ethanol immersion is performed 2 to 4 times, the duration of each ethanol immersion is 8 to 12 hours, and the vacuum drying is performed at 120 to 150° C. for 8 to 12 hours.
[0016] The present invention also provides a light-humidity responsive MOFs composite material prepared by the preparation method.
[0017] The present invention also provides an application of a light-humidity responsive MOFs composite material in CO2 adsorption.
[0018] Among them, the photoresponsive mechanism of the above-mentioned light-and-humidity responsive MOFs composite materials in CO2 adsorption is: under light conditions, the photosensitive groups in the MOFs material can achieve effective separation of excited electrons and holes through charge transfer, adjust the electron density distribution and surface electrostatic potential of the adsorption active sites, and then effectively intervene and regulate the adsorption active sites of MOFs, thereby realizing efficient adsorption of CO2 by light-responsive MOFs materials.
[0019] The wet response mechanism of the above-mentioned light-wet response MOFs composite material in CO2 adsorption is as follows: due to the strong interaction between the MOFs bridging group μx-OH and water molecules through hydrogen bonds, water molecules are adsorbed on the μx-OH group, resulting in a reduction in the MOFs pore size, partial blockage of the pores, and restricted diffusion of CO2 molecules, thereby promoting the effective accommodation of CO2 molecules. In addition, the adsorbed water molecules can be secondary adsorption sites, and further adsorb CO2 through hydrogen bond interactions and hydration reactions, and finally achieve the enhancement of the pore capacity for CO2 through the water molecule confinement mechanism; under anhydrous conditions, a CO2 molecule needs to bind to two amino groups, while under humid conditions, the presence of water vapor causes carbon dioxide to hydrate to form bicarbonate, and a bicarbonate molecule only needs to bind to one amino group, so water molecules increase the utilization rate of amino groups, and the CO2 adsorption capacity is enhanced due to the water molecule strengthening amino group mechanism. Finally, the dual mechanism (water molecule confinement mechanism and water molecule strengthening amino group mechanism) is coupled to enhance the adsorption of carbon dioxide by MOFs materials.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] The light-humidity responsive MOFs composite material provided by the present invention combines the dual advantages of light response and humidity response, and can significantly improve the adsorption capacity of CO2 under the conditions of light and humidity changes. The adsorption process is driven by clean energy such as solar energy, which reduces the energy consumption cost of traditional adsorption technology and conforms to the concept of green and sustainable development. The composite material can be widely used in the fields of industrial flue gas, air separation, etc., and provides a new solution for the capture and storage of CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a graph showing the CO2 transmission curves at different humidity levels of the light-humidity responsive MOFs composite material prepared in Example 1 of the present invention;
[0024] Figure 2 This is the CO2 adsorption isotherm diagram of the light-humidity responsive MOFs composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0029] The terms "include", "comprising", "having", "containing" and the like used herein are all open-ended terms, which mean including but not limited to. The room temperature described below is 25°C.
[0030] The present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0031] (1) ZrCl4, 2-aminoterephthalic acid and tetrakis(4-carboxyphenyl)porphyrin are placed in a microwave reaction tube, N,N-dimethylformamide (DMF) and acetic acid are added, and stirred at room temperature for 10-25 minutes to obtain a solution;
[0032] (2) Add Eu(NO3)3·6H2O to the above solution and continue stirring at room temperature for 10-25 minutes to obtain a mixed solution;
[0033] (3) transferring the mixed solution into a microwave reactor and performing microwave synthesis at 110-130° C. for 1-4 h;
[0034] (4) The reaction product of step (3) is centrifuged, and then washed with ethanol at room temperature for 2-4 times, each time for 8-12 hours, and then vacuum dried at 120-150° C. for 8-12 hours to obtain a light-humidity responsive MOFs composite material.
[0035] Wherein, the molar ratio of the above-mentioned ZrCl4, Eu(NO3)3·6H2O, 2-aminoterephthalic acid, tetrakis(4-carboxyphenyl)porphyrin, acetic acid and DMF is (1.1-1.5):(0.2-0.8):1:(0.15-0.2):(30-60):(220-300).
[0036] The present invention will be further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0037] Example 1
[0038] Embodiment 1 of the present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0039] 0.237g ZrCl4, 0.123g 2-aminoterephthalic acid and 0.112g tetrakis(4-carboxyphenyl)porphyrin were placed in a microwave reaction tube, 15mL DMF and 2mL acetic acid were added, stirred at room temperature for 20min, then 0.151g Eu(NO3)3·6H2O was added, and stirring at room temperature for 20min was continued. The resulting mixed solution was transferred into a microwave reactor and microwaved at 120°C for 3h. After that, the product was centrifuged, washed with ethanol at room temperature for 4 times, each time for 10h, and then vacuum dried at 150°C for 10h to obtain a light-humidity responsive MOFs composite material.
[0040] The CO2 transmission curves of the light-humidity responsive MOFs composite material finally prepared in this embodiment at different humidity are shown in FIG. Figure 1 As shown by Figure 1 It can be seen that with the increase of humidity, the CO2 adsorption capacity of the light-humidity responsive MOFs composite material prepared in this embodiment is improved, and its CO2 adsorption capacity under a humidity of 50% increases from 0.58 mmol / g under dry conditions to 1.12 mmol / g.
[0041] The CO2 adsorption isotherm of the light-humidity responsive MOFs composite material finally prepared in this embodiment is as follows: Figure 2 As shown by Figure 2 It can be seen that at 298K and 1 bar, when changing from darkness to light, the CO2 static adsorption capacity of the light-humidity responsive MOFs composite material prepared in this embodiment can increase from 3.05mmol / g to 4.51mmol / g. Therefore, the light-humidity responsive MOFs composite material provided by the present invention can significantly improve the adsorption capacity of CO2 under the conditions of light and humidity changes.
[0042] Example 2
[0043] Embodiment 2 of the present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0044] 0.158g ZrCl4, 0.123g 2-aminoterephthalic acid and 0.0894g tetrakis(4-carboxyphenyl)porphyrin were placed in a microwave reaction tube, 15mL DMF and 2mL acetic acid were added, stirred at room temperature for 20min, then 0.151g Eu(NO3)3·6H2O was added, and stirring at room temperature was continued for 20min. The resulting mixed solution was transferred into a microwave reactor and microwaved at 120°C for 2h. After that, the product was centrifuged, washed with ethanol at room temperature for 4 times, each time for 10h, and then vacuum dried at 140°C for 10h to obtain a light-humidity responsive MOFs composite material.
[0045] Example 3
[0046] Embodiment 3 of the present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0047] 0.174 g ZrCl4, 0.123 g 2-aminoterephthalic acid and 0.112 g tetrakis(4-carboxyphenyl)porphyrin were placed in a microwave reaction tube, 12 mL DMF and 2 mL acetic acid were added, stirred at room temperature for 20 min, and then 0.242 g Eu(NO3)3·6H2O was added, and stirring at room temperature for 10 min. The resulting mixed solution was transferred into a microwave reactor and microwaved at 110°C for 4 h. After that, the product was centrifuged, washed with ethanol at room temperature twice, each time for 12 h, and then vacuum dried at 120°C for 12 h to obtain a light-humidity responsive MOFs composite material.
[0048] Example 4
[0049] Embodiment 4 of the present invention provides a method for preparing a light-humidity responsive MOFs composite material, comprising the following steps:
[0050] 0.237g ZrCl4, 0.123g 2-aminoterephthalic acid and 0.081g tetrakis(4-carboxyphenyl)porphyrin were placed in a microwave reaction tube, 16mL DMF and 2mL acetic acid were added, stirred at room temperature for 15min, then 0.061g Eu(NO3)3·6H2O was added, and stirring at room temperature for 20min was continued. The resulting mixed solution was transferred into a microwave reactor and microwaved at 130°C for 2h. After that, the product was centrifuged, washed with ethanol at room temperature for 3 times, each time for 10h, and then vacuum dried at 130°C for 10h to obtain a light-humidity responsive MOFs composite material.
[0051] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a light-humidity responsive MOFs composite material, characterized in that: The following steps are involved: (1) ZrCl4, 2-aminoterephthalic acid and tetrakis(4-carboxyphenyl)porphyrin are placed in a microwave reaction tube, N,N-dimethylformamide (DMF) and acetic acid are added, and stirred to obtain a solution; (2) adding Eu(NO3)3·6H2O to the solution in step (1) and continuing stirring to obtain a mixed solution; (3) moving the mixed solution into a microwave reactor and performing microwave synthesis to obtain a reaction product; (4) The reaction product obtained in step (3) is centrifuged, washed with ethanol and vacuum dried to obtain a light-moisture responsive MOFs composite material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of ZrCl4, Eu(NO3)3·6H2O, 2-aminoterephthalic acid, tetrakis(4-carboxyphenyl)porphyrin, acetic acid and DMF is (1.1-1.5):(0.2-0.8):1:(0.15-0.2):(30-60):(220-300).
3. The preparation method according to claim 1, characterized in that: In step (1), the stirring reaction is carried out at room temperature for 10-25 minutes.
4. The preparation method according to claim 1, characterized in that: In step (2), the stirring reaction is carried out at room temperature for 10-25 minutes.
5. The preparation method according to claim 1, characterized in that: In step (3), the microwave synthesis condition is 110-130° C. for 1-4 h.
6. The preparation method according to claim 1, characterized in that: In step (4), the ethanol immersion is performed 2 to 4 times, and the duration of each ethanol immersion is 8 to 12 hours. The vacuum drying is performed at 120 to 150° C. for 8 to 12 hours.
7. A light-humidity responsive MOFs composite material prepared by the preparation method according to any one of claims 1 to 6.
8. Application of the light-humidity responsive MOFs composite material as described in claim 9 in CO2 adsorption.